Changes in Relative Wages, 1963-1987: Supply and Demand Factors - Katz, L. F.; Murphy, K. M. (Quarterly Journal of Economics, 1992)
A simple supply and demand framework is used to analyze changes in the U. S. wage structure from 1963 to 1987. Rapid secular growth in the demand for more-educated workers, “more-skilled” workers, and females appears to be the driving force behind observed changes in the wage structure. Measured changes in the allocation of labor between industries and occupations strongly favored college graduates and females throughout the period. Movements in the college wage premium over this period appear to be strongly related to fluctuations in the rate of growth of the supply of college graduates.